Effect of First Heater Temperature Variations on the Polyester Yarn Properties of False -Twist Texturing Techniques - (:unkn) unknown (INST CHEMICAL FIBRES, 2009)
In this study; poly (ethylene terephthalate) PET POY, with 140 dtex 36 f and 295 dtex 36 f were used for the production textured yarns of 83 dtex 36 f and 167 dtex 36 f. The yarn were textured at a first heater temperature of 175 degrees C 190 degrees C and 205 degrees C set in both false-twist texturing machines, the Muratec 33 H (Belt-type nip twisters) and Barmag FK 6 M-1000 (Disk-type twisters)Afterwards the resulting 83 dtex 36 f and 167 dtex 36 f textured yarns were examined by measuring their tenacity, elongation at break, crimp contraction, crimp module, crimp stability, and shrinkage of yarns in boiling water. Afterwards, conclusions were drawn using the test values. The result was that, as the first heater temperature increases, the value of crimp contraction, crimp module and crimp stability of textured yarns increases, while the shrinkage values decrease. Generally, it was observed that regardless of the first heater temperature the tenacity and elongation change only slightly.
Keywords: texturing machines; textured yarns; heater temperature; breaking tenacity; crimp contraction; polyester (PET); elongation at break